Fostering the Aesthetic Pleasure: The Effect of Verbal Description on Aesthetic Appreciation of Ambiguous and Unambiguous Artworks - Emanuela Mari (MDPI AG, 2021)
Background: Aesthetic experience begins through an intentional shift from automatic visual perceptual processing to an aesthetic state of mind that is evidently directed towards sensory experience. In the present study, we investigated whether portrait descriptions affect the aesthetic pleasure of both ambiguous (i.e., Arcimboldo’s portraits) and unambiguous portraits (i.e., Renaissance portraits). Method: A total sample of 86 participants were recruited and completed both a baseline and a retest session. In the retest session, we implemented a sample audio description for each portrait. The portraits were described by three types of treatment, namely global, local, and historical descriptions. Results: During the retest session, aesthetic pleasure was higher than the baseline. Both the local and the historical treatments improved the aesthetic appreciation of ambiguous portraits; instead, the global and the historical treatment improved aesthetic appreciation of Renaissance portraits during the retest session. Additionally, we found that the response times were slower in the retest session. Conclusion: taken together, these findings suggest that aesthetic preference was affected by the description of an artwork, likely due to a better knowledge of the painting, which prompts a more accurate (and slower) reading of the artwork.